Upaya Penurunan Kejadian Karies Gigi pada Anak Melalui Colouring Book sebagai Media Health Education di Sekolah Dasar Wilayah Gresik - Diah Fauzia Zuhroh; Diah Jerita Eka Sari; Ernawati Ernawati; Yusuf Hermansyah; Ainul Mufidah (PT.Mantaya Idea Batara, 2021)
The incidence of dental and oral health problems in school-age children is still quite high, so it is necessary to provide health education with appropriate media for them. The results of the survey at Madrasah Ibtidayyah Negeri 1 Gresik class 1 showed that 80% of children had cavities. None of the students' teeth were filled. 64% of children have tooth decay / teeth, and this triggers the high incidence of dental infections in children. 80% of children brush their teeth twice a day. 63% of children do not have the habit of brushing their teeth before going to bed. The response through a digital survey to the use of health education media in the form of coloring books makes children happy and is expected to increase children's desire to maintain dental health as in the book